Assessing the genetic diversity of finger millet (Eleusine coracana) germplasm for agronomic traits - SINGH, ANOOP; SEHRAWAT, KRISHAN D; SEHRAWAT, ANISH; SINGH, MANJEET; RANI SEHRAWAT, ANITA (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during the rainy (kharif) season of 2019 and 2020 at research farm of CCS Haryana Agricultural University Hisar, Haryana to assess the genetic diversity of finger millet [Eleusine coracana (L.) Gaertn.] germplasm for agronomic traits. Experiment consisted of 150 accessions and 4 checks in augmented block design. The analysis of variance (ANOVA) divulged that test genotypes showed a highly significant difference (P<0.01) for agronomic traits. A maximum (96.67) heritability (hBS) was observed for days to 50% flowering, followed by 1000-grains weight (94.93). The least hBS (68.37) was observed for flag leaf blade width. Genetic advance over mean (GAM) was the maximum for grain yield per plant (99.51), followed by harvest index (65.59) and ear head width (59.22), productive tillers (55.54), 1000-grains weight (36.74), flag leaf blade width (25.19) and plant height (24.92) while the other traits like day to 50% flowering, days to maturity, fingers number on the main ear, peduncle length and flag leaf blade width showed less than 20% of GAM. Principal Component Analysis (PCA) revealed that the first 5 PCs with eigenvalues greater than unity, hold 74.07% total variability. Hierarchical clustering was also carried and top 10 promising accessions were identified. Hence, the current research revealed that the selected finger millet accessions were highly diverse for grain yield and other studied agronomic traits, which favour selection and could be utilized in different breeding programs.